„Wyobrażenia geopolityczne” jako przedmiot badań współczesnej geografii politycznej - Potulski, Jakub (Civitas. Studia z filozofii polityki, 2019)
The theories of Henri Lefebvre on the Production of Space have influenced our understanding of the ontology of space. The processes of constructing and “appropriating” space are important elements of man’s political activity. Space is not neutral: its alleged objectivity is treated in a voluntary manner, depending on political demand. The importance given to geographical space and the supposed “laws” governing history are instruments of political indoctrination or propaganda justification of the pursued policy pursued. Space is political and ideological. Borders, political maps and states are the products of human political activity; they are “socially produced”. In contemporary political geography, the theme of “the production of space” is very popular. The main goal of the article is to analyse the currently important research category – “geographical imaginations”. This category is mainly used to understand our perception of space and the roots of political conflicts.